The Case for an Integrated Healthcare Regulatory Authority in Assam: Enhancing Quality and Standardization in Private Healthcare Establishments - Pallathadka, Harikumar; Roy, Parag Deb; Chowdhury, Saumya Shankar (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Background: The private healthcare sector in Assam has expanded substantially in recent decades, yet regulatory oversight remains fragmented across multiple authorities with overlapping jurisdictions. This fragmentation has led to inconsistent quality standards, enforcement challenges, and suboptimal patient outcomes. This paper examines the limitations of the current regulatory framework and proposes the establishment of a unified Healthcare Regulatory Authority to comprehensively oversee private healthcare establishments including hospitals, nursing homes, clinics, diagnostic centers, and pharmacies. Methods: This study employed a mixed-methods approach combining: (1) systematic review of existing regulatory frameworks in Assam and successful models from other Indian states (n=6); (2) analysis of compliance data from 423 private healthcare establishments across all 33 districts of Assam; (3) structured interviews with 57 key stakeholders representing diverse perspectives; and (4) comparative quality assessment across differently regulated facilities using standardized tools adapted from NABH and NABL frameworks. Gap analysis methodology was used to identify regulatory deficiencies and their impact on healthcare quality. Statistical analyses included descriptive statistics, comparative analyses, correlation analyses, and multiple regression modeling to establish relationships between regulatory approaches and quality metrics. Results: The current regulatory landscape in Assam is characterized by jurisdictional ambiguity (overlap score: 0.76), inconsistent standards application (standardization gap: 0.82), limited enforcement capacity (compliance rate: 46.8%), and significant quality variations across facilities (quality standard deviation: 28.7%). Facilities under fragmented oversight demonstrated significantly lower quality scores (mean difference: 18.4 points, p<0.001) compared to those with integrated oversight. Multiple regression analysis identified regulatory fragmentation as a significant predictor of poor quality outcomes (standardized β=-0.38, p<0.001). Stakeholder interviews revealed strong support (87.3%) for a unified regulatory authority with comprehensive jurisdiction, citing reduced regulatory burden, enhanced quality standardization, improved accountability, and streamlined compliance processes as anticipated benefits. Conclusion: This study presents compelling evidence for establishing an Assam Healthcare Regulatory Authority (AHRA) as a centralized body to oversee registration, standardization, and quality assurance across all private healthcare establishments. The proposed authority would provide unified licensing, standardized protocols, centralized monitoring, and transparent enforcement mechanisms to enhance healthcare quality while reducing regulatory burden. Implementation would require comprehensive enabling legislation, phased integration of existing authorities, significant capacity development, sustained stakeholder engagement, and evidence-based policy formulation. This integrated approach aligns with successful models from other Indian states that have demonstrated substantial improvements in healthcare quality, compliance rates, and operational efficiency.